PENGARUH CONTEXTUAL TEACHING AND LEARNING TERHADAP MINAT BELAJAR INFORMATIKA DASAR PADA SISWA KELAS X JURUSAN KULINER SMK NEGERI 3 KUPANG - Malelak, Jedidya; J. Takuneno, Katrin; Y.A Fallo, Diana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of the Contextual Teaching and Learning (CTL) model on students' learning interest in Basic Informatics subjects at the Culinary Department of SMK Negeri 3 Kupang. The research was motivated by the low learning interest of students in Basic Informatics, which affects their participation and engagement during the learning process. This study employed a quantitative approach using a quasi-experimental method with a One Group Pretest–Posttest Design. The sample consisted of 23 students from Class X Culinary 3 selected through cluster sampling. Data were collected using a learning interest questionnaire administered before and after the implementation of the CTL model. The collected data were analyzed using descriptive statistics, normality testing, and Paired Sample t-Test. The findings indicated that the implementation of the CTL model positively influenced students' learning interest. Students demonstrated increased enthusiasm, attention, participation, and engagement in learning activities after the application of CTL. The contextual learning process, which connected Basic Informatics materials with real-life situations and culinary vocational contexts, helped students understand the relevance of the subject matter and increased their motivation to learn. Therefore, the CTL model can be considered an effective learning approach for improving students' learning interest in Basic Informatics subjects at vocational schools.